THE EFFECT OF PROFITABILITY, LIQUIDITY, SOLVABILITY, AND ACTIVITY ON STOCK PRICES - Maharani, Gama Sita; Mujiyati, Mujiyati (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to examine the effect of profitability (NPM), liquidity (CR), solvency (DER), and activity (TATO) on stock prices (closing price) of consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period. A quantitative approach was applied using secondary data from financial reports obtained through official IDX documentation and company websites. The sample was selected using purposive sampling based on specific criteria, such as financial reports in Indonesian Rupiah, positive net income, and complete data availability. Data analysis was conducted using SPSS 25, employing multiple linear regression preceded by classical assumption tests. The results indicate that profitability and activity have a significant positive effect on stock prices, while liquidity and solvency show no significant effect. These findings suggest that operational efficiency and the ability to generate profit are key factors influencing investor interest. Keywords: Activity; Liquidity; Profitability; Solvency; Stock Price